2018
DOI: 10.3389/fpsyg.2018.01569
|View full text |Cite
|
Sign up to set email alerts
|

The Big-Fish-Little-Pond Effect on Academic Self-Concept: A Meta-Analysis

Abstract: The Big-fish-little-Pond effect is well acknowledged as the negative effect of class/school average achievement on student academic self-concept, which profoundly impacts student academic performance and mental development. Although a few studies have been done with regard to this effect, inconsistence exists in the effect size with little success in finding moderators. Here, we present a meta-analysis to synthesize related literatures to reach a summary conclusion on the BFLPE. Furthermore, student age, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 71 publications
(91 reference statements)
7
71
1
1
Order By: Relevance
“…Because support for generalizability is an important aspect of the present investigation, we present estimates of the BFLPE (Table ) on the basis of four PISA data collections between 2000 and 2012 (PISA 2000: Marsh & Hau, : 103 558 students from 26 countries; PISA 2003: Seaton, Marsh, & Craven, , : 265 180 students from 41 countries; PISA 2006: Nagengast & Marsh, : 397 500 students from 57 countries; PISA 2012: Marsh, Parker, & Pekrun, : 485, 490 from 68 countries/regions). In all but one of the 191 samples, school‐average achievement had a negative effect on ASC and was significantly negative in 181 samples (also refer to recent meta‐analysis of BFLPE studies by Fang et al, ). The BFLPE tends to increase during the period that students attend the same high school (Marsh, Köller, & Baumert, ) and is maintained after students graduated from high school (Marsh, Trautwein, Lüdtke, Baumert, & Köller, ).…”
Section: The Importance Of the Self‐concept Constructmentioning
confidence: 95%
See 1 more Smart Citation
“…Because support for generalizability is an important aspect of the present investigation, we present estimates of the BFLPE (Table ) on the basis of four PISA data collections between 2000 and 2012 (PISA 2000: Marsh & Hau, : 103 558 students from 26 countries; PISA 2003: Seaton, Marsh, & Craven, , : 265 180 students from 41 countries; PISA 2006: Nagengast & Marsh, : 397 500 students from 57 countries; PISA 2012: Marsh, Parker, & Pekrun, : 485, 490 from 68 countries/regions). In all but one of the 191 samples, school‐average achievement had a negative effect on ASC and was significantly negative in 181 samples (also refer to recent meta‐analysis of BFLPE studies by Fang et al, ). The BFLPE tends to increase during the period that students attend the same high school (Marsh, Köller, & Baumert, ) and is maintained after students graduated from high school (Marsh, Trautwein, Lüdtke, Baumert, & Köller, ).…”
Section: The Importance Of the Self‐concept Constructmentioning
confidence: 95%
“…This perspective is central to the social comparison theory (Festinger, ) in psychology and has also been influential in sociology and economics. Extending this theoretical work, Marsh (; also Fang et al, ; Marsh & Parker, ; Marsh et al, ) proposed the big‐fish‐little‐pond effect (BFLPE), in which students show lower ASCs when placed in a context of high‐ability students but higher ASCs when placed in a context of low‐ability students. Increasingly sophisticated theoretical and statistical models of ASC development, based in part on this BFLPE, have demonstrated that frame‐of‐reference effects occur at the school and country levels, as well as the individual‐student level (Marsh, ; Marsh et al, ; Marsh & Seaton, ).…”
Section: The Importance Of the Self‐concept Constructmentioning
confidence: 99%
“…The frame of reference for unselected adolescents is normal distribution of conscientiousness that they see in their peers. In contrast, the selected schoolchildren in Sirius may be influenced by their exposure to a group of highly selected adolescents, which may lead to lower self-perceived conscientiousness (i.e., being a small fish in a big pond; Fang et al, (2018)). In addition, the lower conscientiousness in gifted adolescents may result from their negative experiences with peers.…”
Section: Differences Between Selected and Unselected Samplesmentioning
confidence: 99%
“…However, the extent to which meta-analyses can provide evidence for the crossnational generalizability of an effect depends substantially on the degree to which the individual studies contained within it represent samples from varied countries. Indeed, the only known metaanalysis on the BFLPE to date (Fang et al, 2018), while consisting of studies using varied samples for math and science subjects, consisted largely of Western, educated, industrialized, rich and democratic (WEIRD) samples for reading self-concept (with 10 effect sizes from Europe and America, and two from Asia). The use of large-scale cross-national datasets, such as the PISA data used here, overcome such drawbacks of meta-analysis (see Marsh et al 2020 for a detailed discussion on the juxtaposition of meta-analytic studies and cross-national studies based on PISA data).…”
Section: Cross-national Generalizability Of Resultsmentioning
confidence: 99%